Spatial rolling contact pair with a hybrid elastic constraint composed of flexible bands and linear springs - Naoto KIMURA (The Japan Society of Mechanical Engineers, 2019)
Spatial rolling contact pair (SRCP) is a kinematic pair of which two links in contact at a line can generate the relative rolling motion along the specified spatial trajectory. By introducing the SRCP into a linkage mechanism with a single degree-of-freedom (DOF), the mechanism can completely generate the specified output motion. However, the conventional constraint method between two links of the SRCP is not strong enough. In order to enforce the connection between the two links, the novel design of the SRCP which has a hybrid elastic constraint with flexible bands and linear springs is proposed. Since flexible bands and linear springs can suppress slippage and separation between the two links, the SRCP can generate the ideal rolling motion. At first, the design methodology of the rolling contact surfaces of the SRCP, which has been proposed by the authors, is reviewed. Next, it is confirmed that constraint with flexible bands can be applied to the designed surfaces with a mathematical approach. In addition, the design methodology of the flexible bands to generate the zero torque around the contact line between the two links is described. Then, the design methodology for the constraint with linear springs is proposed. In this methodology, linear springs are optimally arranged between links so that two links in the SRCP can keep in contact at a line. Some examples of path generators with the SRCP are designed with the proposed design methodology, and it is confirmed that the SRCPs can generate the ideal rolling motion by some simulations. Finally, the designed examples are fabricated and examined to confirm the validity of the proposed design methodology.